DERECHO, SISTEMA Y LEGITIMACIÓN. LA PROPUESTA HABERMASIANA: LA SUPERACIÓN INDIVIDUALISTA DEL "SUJETO" POR LA CATEGORÍA DE LA "INTERSUBJETIVIDAD" - Cesário dos Santos, Admaldo (2021)
The paper approaches the question of the legitimacy of the right from the functionalism, comparing the concepts of subjectivity in the visions of Luhmann and Habermas and of how there can be a true democracy in the present societies. It takes into consideration how the subjective action should be given to achieve this legal-democratic legitimation.